Risk assessment of biological hazards in University laboratories: checklist and critical control points - De Felice, M.; D'Abramo, M.; Mormile, P.; Scatigna, M.; Bianchi, S.; Fabiani, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background and aim. Biomedical research in academic settings is an important issue for Public Health and Environment protection. As workplaces, the facilities for research expose their personnel to different hazards and health risks. The University of L’Aquila (Italy) carried out a field study aimed at creating and applying a checklist intended for laboratory staff. Methods. The proposed checklist was derived from the procedure illustrated in the Appendix (procedure followed for the identification of a numerical index of biological risk for university facilities) and consists of 9 items. The study was conducted in 42 laboratories. Results. The results highlighted that 40 laboratories fall into the “low risk” and the remaining 2 into the “moderate risk” category. Conclusions. Labs with risk factors are a minority. These were properly identified using the proposed methodology.